The Different Dynamics of Femicide in a Small Nordic Welfare Society - Freysteinsdóttir, Freydís Jóna (Qualitative Sociology Review, 2017)
In this study, all cases of femicide in Iceland over a thirty-year period were explored. A total of sixteen women and girls were killed during the years 1986-2015. Femicide was defined in this study as the murder of a woman by a partner, former partner, or because of passion. According to this definition, eleven femicide cases occurred during this time period. The data analyzed were court verdicts and news reports of the incidents. Qualitative methods were used for analysis. Interestingly, there was a different dynamic related to femicide cases, which included 1) sex femicide, 2) former partners and 3) current partners. Alcohol consumption and the willingness of the victim to end sex appear to be a dangerous mixture, judging from the results of the sexually-related femicide cases. Alcohol consumption was a factor in all current partner femicide cases in addition to low SES status; empathy was lacking, and patriarchal views were prominent in some of them. In former partner femicide cases, jealousy and possessiveness were major themes, but not alcohol consumption. It is important to study such dynamics and contextual factors in greater detail in larger studies.